MADS-Box Transcription Factor VdMcm1 Regulates Conidiation, Microsclerotia Formation, Pathogenicity, and Secondary Metabolism of Verticillium dahliae - Xiong, Dianguang; Wang, Yonglin; Tian, Longyan; Tian, Chengming (Frontiers in Microbiology, 2016)
Verticillium dahliae, a notorious phytopathogenic fungus, causes vascular wilt diseases in many plant species resulting in devastating yield losses worldwide. Due to its ability to colonize plant xylem and form microsclerotia, V. dahliae is highly persistent and difficult to control. In this study, we show that the MADS-box transcription factor VdMcm1 is a key regulator of conidiation, microsclerotia formation, virulence, and secondary metabolism of V. dahliae. In addition, our findings suggest that VdMcm1 is involved in cell wall integrity. Finally, comparative RNA-Seq analysis reveals 823 significantly downregulated genes in the VdMcm1 deletion mutant, with diverse biological functions in transcriptional regulation, plant infection, cell adhesion, secondary metabolism, transmembrane transport activity, and cell secretion. When taken together, these data suggest that VdMcm1 performs pleiotropic functions in V. dahliae.